The thirteenth step : addiction in the age of brain science. - Heilig, Markus (Columbia University Press, 2015)
The past twenty-five years have witnessed a revolution in the science of addiction, yet we still rely upon sorely outdated methods of treatment. Expensive new programs for managing addiction are also flourishing, but since they are not based in science, they offer little benefit to people who cannot afford to lose money or faith in their recovery. Clarifying the cutting-edge science of addiction for practitioners and general readers, The Thirteenth Step pairs stories of real patients with explanations of key concepts relating to their illness. A police chief who disappears on the job illustra.